Posterolateral Fractures of the Tibial Plateau Revisited: A Simplified Treatment Algorithm - Giordano, Vincenzo; Pires, Robinson Esteves; Pimenta, Frederico Silva; Campos, Túlio Vinícius de Oliveira; Andrade, Marco Antônio Percope de; Giannoudis, Peter V. (The Journal of Knee Surgery, 2020)
High-energy fractures of the proximal tibia with extensive fragmentation of the posterolateral (PL) quadrant of the tibial plateau are challenging to manage. Herein, we present a review of the literature on the patterns and options of approach and fixation of the PL fragment of the tibial plateau to optimize the treatment of this specific injury pattern. We searched PubMed (1980–May 2020) to identify and summarize the most relevant articles evaluating both the morphology and treatment recommendations, including the choice of approach and fixation strategy, for the PL tibial plateau fracture. We found PL fragment can present in several patterns as a pure split, split depression, contained pure depression, and noncontained depression (rim crush), which are mostly determined by the position of the knee and the force magnitude applied during the course of the accident. Based on previous concepts described by Schatzker and Kfuri, we suggest a simplified treatment algorithm highlighting the two concepts (buttressing and containment) used for plating the PL tibial plateau fragments. Based on the available current evidence, we propose an algorithm for these two morphological types of PL tibial plateau fracture. Shear-type fractures need buttressing (the “rule of thumb”), whereas noncontained peripheral rim-type fractures need peripheral repair and containment. Contained pure depression fractures are not frequent and need percutaneous-assisted elevation and subchondral rafting, either controlled by fluoroscopy or arthroscopically. It is believed that such an approach would simplify their assessment and preoperative planning and would assist the clinicians to appreciate and manage more consistently these complex injuries.
Keywords: tibial plateau; tibial plateau fracture; posterolateral corner; treatment algorithm; treatment strategy